Cutaneous leiomyosarcoma on the face - Nathalia Dias Negrão Murback; Luiz C. Takita; Bruna Corrêa de Castro; Gunter Hans Filho (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Leiomyosarcoma is a rare skin tumor, most common in white men in the fifth to eighth decades of life. Primary tumors are classified in dermal or subcutaneous, that differ by clinical and prognostic features. They may appear on any site of the body, but are rare on the face. A 54-year-old female was admitted with a 5cm exophytic nodular lesion of 8 months duration on the right cheek, site of previous chronic radiodermatitis. Histopathology revealed spindle-shaped cell neoplasia, positive for smooth muscle actin on immunohistochemistry. Cutaneous leiomyosarcomas on the face are rare and may occur in previously irradiated areas. Immunohistochemistry is mandatory for an accurate diagnosis. Its similarity with other tumors may complicate the diagnosis, with delay expansion of the tumor.